2016
DOI: 10.1534/g3.116.035196
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila CG2469 Encodes a Homolog of Human CTR9 and Is Essential for Development

Abstract: Conserved from yeast to humans, the Paf1 complex participates in a number of diverse processes including transcriptional initiation and polyadenylation. This complex typically includes five proteins: Paf1, Rtf1, Cdc73, Leo1, and Ctr9. Previous efforts identified clear Drosophila homologs of Paf1, Rtf1, and Cdc73 based on sequence similarity. Further work showed that these proteins help to regulate gene expression and are required for viability. To date, a Drosophila homolog of Ctr9 has remained uncharacterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…1E), suggesting they act downstream of PIWI-initiated silencing in fly ovaries. Since ATU is the homolog of Leo1, a component of the yeast PAF1 complex, we tested other Drosophila PAF1 complex factors, such as PAF1, RTF1, CTR9 (also called CG2469, [28, 29]), and HYRAX (HYR, homolog of CDC73 [30]). Only HYR knockdown impaired PIWI-directed silencing, while CTR9 knockdown lacked impact on the Flam reporters (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1E), suggesting they act downstream of PIWI-initiated silencing in fly ovaries. Since ATU is the homolog of Leo1, a component of the yeast PAF1 complex, we tested other Drosophila PAF1 complex factors, such as PAF1, RTF1, CTR9 (also called CG2469, [28, 29]), and HYRAX (HYR, homolog of CDC73 [30]). Only HYR knockdown impaired PIWI-directed silencing, while CTR9 knockdown lacked impact on the Flam reporters (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Homozygous mutants and whole-fly knockdowns of Drosophila PAF1 factors are lethal [2830, 32]. To test the impact of Drosophila PAF1 in ovary development, we used transgenic RNAi to knock down dPaf1 and dRtf1 with germline Nos-Gal4 and soma Tj-Gal4 drivers (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…yeast) and multicellular organisms when CTR9 is depleted. While Ctr9 is not an essential gene in S. cerevisiae (Chen et al, 2002; Massoni-Laporte et al, 2012), CTR9 knockout causes early embryonic lethality in higher eukaryotic organisms such as Drosophila (Chaturvedi et al, 2016), zebrafish (Akanuma et al, 2007) and mouse (Zhang et al, 2013). The requirement of CTR9 in preimplantation development of mice resembles the phenotypes that result from lacking core PRC2 subunits SUZ12, EZH2 and EED (Pasini et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In the female GSCs, it has recently been shown that the global level of H3K4me3 is decreased upon loss-of-function of the Drosophila ortholog of Ctr9, a component of the Paf1 complex normally required for transcriptional initiation and polyadenylation. However, the functional readout of this global H3K4me3 loss remains unclear ( Chaturvedi et al 2016 ).…”
Section: Mechanisms Regulating Gsc Self-renewal Vsmentioning
confidence: 99%